MODERN VISUALLY EFFECTIVE TOOLS FOR BUILDING QUANTITATIVE CONCEPTS IN KINDERGARTEN CHILDREN: Received: 15th July 2025, Revised: 08th September 2025, Accepted: 10th November 2025, 20th November 2025, Date of Publication: 27th November 2025 - Maria Petrova Temnikova (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Digitalization and the rapid development of information and communication technologies over the past decades have significantly changed social life and the conditions in which preschool education is carried out. By using different aids for visualization in teaching, the contradiction between the abstract nature of mathematical concepts that children learn in kindergarten and their concrete-active and visual-imaginative thinking is overcome. The modernization of education in mathematics in kindergarten is related not only to the application of innovative technologies and approaches but also to the contemporary tools that are used. The problem of selecting them and using them adequately in methodological work exists and is significant. The aim of the research work is to analyze and systematize theoretical concepts related to modern visual-active tools and to develop and test methodological options for their application in building quantitative understanding in children in kindergarten. The empirical study was conducted with 128 children from a kindergarten in the town of Stara Zagora. The obtained results show that the use of modern visual-active tools supports the development of children’s knowledge and skills regarding the quantitative and ordinal value of numbers up to 10, the formation and comparison of sets through the relations "as many as," "more," "less," the subtraction or addition of 1 or 2 elements from a given set, and the modeling of numbers up to 10. The new educational paradigm requires the application of modern visual-active tools in preschool education in mathematics, which contributes to improving the level of knowledge and skills of children in the educational Cluster "Quantitative Relations," as well as their interest, activity, and motivation.